2015
DOI: 10.1111/cogs.12247
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Linguistic Differences in Processing Double‐Embedded Relative Clauses: Working‐Memory Constraints or Language Statistics?

Abstract: An English double‐embedded relative clause from which the middle verb is omitted can often be processed more easily than its grammatical counterpart, a phenomenon known as the grammaticality illusion. This effect has been found to be reversed in German, suggesting that the illusion is language specific rather than a consequence of universal working memory constraints. We present results from three self‐paced reading experiments which show that Dutch native speakers also do not show the grammaticality illusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(118 citation statements)
references
References 34 publications
10
104
0
Order By: Relevance
“…In this model, which we call noisy-context surprisal, the processing cost of a word is the surprisal of the word given a noisy representation of the preceding context. We show that this model accounts for an outstanding puzzle in sentence comprehension, language-dependent structural forgetting effects (Gibson and Thomas, 1999;Vasishth et al, 2010;Frank et al, 2016), which are previously not well modeled by either expectation-based or memory-based approaches. Additionally, we show that this model derives and generalizes locality effects (Gibson, 1998;Demberg and Keller, 2008), a signature prediction of memory-based models.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…In this model, which we call noisy-context surprisal, the processing cost of a word is the surprisal of the word given a noisy representation of the preceding context. We show that this model accounts for an outstanding puzzle in sentence comprehension, language-dependent structural forgetting effects (Gibson and Thomas, 1999;Vasishth et al, 2010;Frank et al, 2016), which are previously not well modeled by either expectation-based or memory-based approaches. Additionally, we show that this model derives and generalizes locality effects (Gibson, 1998;Demberg and Keller, 2008), a signature prediction of memory-based models.…”
mentioning
confidence: 79%
“…The only previous formalized account of language-specific verb forgetting, Frank et al (2016), showed that Simple Recurrent Networks (SRNs) trained on English and Dutch data partly reproduce the verb forgetting effect in the surprisals they assign to the final verb. Our model provides an explanation of the SRN's behavior.…”
Section: Model Of Verb Forgettingmentioning
confidence: 99%
“…We have used this approach to draw inferences from data in previously published work (e.g., Frank, Trompenaars, and Vasishth, 2015, Hofmeister and Vasishth, 2014, Safavi, Husain, and Vasishth, 2016. There are of course other approaches possible for carrying out inference.…”
Section: Inferencementioning
confidence: 99%
“…Staub (2010) has shown that this prediction is correct. The surprisal metric introduced by Hale (2001) thus formalizes the well-established idea of reanalysis that dates back to the early days of psycholinguistics (Frazier, 1979). Surprisal assumes a ranked-parallel parser that ranks the available parses by their conditional probabilities.…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly important to stress-test the expectation-based account given that its predictions sometimes go directly against another, well-established class of explanation, the memory-based accounts of sentence comprehension. Such models attribute processing difficulty to limitations of memory resources (Clifton & Frazier, 1989;Frazier, 1979;Frazier & Fodor, 1978;Gibson, 1998;Gibson, 2000;Just & Carpenter, 1992;Lewis & Vasishth, 2005;Lewis, Vasishth, & Van Dyke, 2006;Miller & Chomsky, 1963). A prominent example for this class of account is the Dependency Locality Theory (DLT) (Gibson, 1998;Gibson, 2000).…”
Section: Introductionmentioning
confidence: 99%